In my research, I found two combinatorial identities. Mathematica can give the answers immediately, but I don't know how to prove them. Could someone help me? Thank you!

Here are they:

Let $\alpha$, $\beta$ be two arbitrary complex numbers, and $k$, $l$ be two positive integers, then:

\begin{align*} \sum_{m=1}^k m \binom{\frac{\alpha+\beta}{\beta}k}{k-m}\binom{\frac{\alpha+\beta}{\beta}l}{l+m} =&\frac{\alpha\,k\,l}{(k+l)(\alpha+\beta)}\binom{\frac{\alpha+\beta}{\beta}k}{k}\binom{\frac{\alpha+\beta}{\beta}l}{l}\\ \sum_{m=1}^k m \binom{\frac{\alpha+\beta}{\beta}k}{k-m}\binom{\frac{\alpha+\beta}{\alpha}l}{l-m} =&\frac{\alpha\,\beta\,k\,l}{(k\,\alpha+l\,\beta)(\alpha+\beta)}\binom{\frac{\alpha+\beta}{\beta}k}{k}\binom{\frac{\alpha+\beta}{\alpha}l}{l} \end{align*}

Actually, the positive integer $l$ can be also a complex number. Then, if one replaces $\frac{\alpha}{\beta}l$ by $\tilde{l}$ in the first identity, it becomes equivalent to the second identity. Besides this observation, I can only prove some trivial cases.

  • 1
    $\begingroup$ In the RHS of the first identity, do you have $\alpha kl $ or rather $\beta kl$? I would expect something depending only on ${\alpha+\beta\over\beta}$, not on $\alpha$ or $\beta$, since so is the LHS. $\endgroup$ – Pietro Majer Feb 5 '17 at 8:32
  • $\begingroup$ I guess dividing by ${ {\alpha+\beta\over\beta} l \choose l}$ both sides in the first identity should give a Vandermonde's identity en.wikipedia.org/wiki/Vandermonde%27s_identity $\endgroup$ – Pietro Majer Feb 5 '17 at 9:09
  • $\begingroup$ @PietroMajer I doubt. This identity is telescoping and Vandermonde's is not (or at least I do not know how it is). $\endgroup$ – Fedor Petrov Feb 5 '17 at 17:54
  • $\begingroup$ Yes; but I suspected the wanted identity may be different (see my first comment) $\endgroup$ – Pietro Majer Feb 5 '17 at 18:59

At first, I reformulate your identity (the first identity, the second is the same up to change of variables, as you note in the post).

Denote $(\alpha+\beta)/\beta=\lambda$ and divide both parts by $\binom{\lambda k}k \binom{\lambda l}l$. We get an equivalent identity $$ \sum_{m=0}^k m\frac{k(k-1)\dots (k-m+1)\cdot (\lambda l-l)\dots (\lambda l-l-m+1)}{(\lambda k-k+1)\dots (\lambda k-k+m)(l+1)\dots(l+m)}=\left(1-\frac1{\lambda}\right)\frac{kl}{k+l}. $$ Denote $\lambda k-k=x$, then $\lambda l-l=xl/k$, $\left(1-\frac1{\lambda}\right)\frac{kl}{k+l}=\frac{kxl}{(k+l)(k+x)}$ and we rewrite your identity as $$ \sum_{m=0}^km\frac{\binom{k}m\binom{xl/k}m}{\binom{-l-1}m\binom{-x-1}m}=\frac{kxl}{(k+l)(k+x)}. $$ Both parts are rational functions in $x$, $l$. The more general hypergeometric identity is $$ \sum_{m=0}^\infty m \frac{\binom{AB}m\binom{CD}m}{\binom{AD-1}m\binom{BC-1}m}=\frac{ABCD}{(A-C)(B-D)} $$ whenever LHS is well-defined, our case correspond to $A=-1,B=-k,C=x/k,D=l$.

UPDATE I proved it with the help of Wolframalpha. This is simply telescoping (here $z$ is old $k$ and $y$ is old $l$): $$m\frac{\binom{z}{m}\binom{xy/z}{m}} {\binom{-x-1}m \binom{-y - 1}{ m}}=h(m-1)-h(m),\\ h(m):=\frac{z(m+x+1)(m+y+1)}{(z+x)(z+y)}\cdot \frac{\binom{z}{m+1}\binom{xy/z}{m+1}}{\binom{-x-1}{m+1}\binom{-y-1}{m+1}}.$$

| cite | improve this answer | |
  • $\begingroup$ Maple 2016 outputs $${\frac {ABCD{\mbox{$_3$F$_2$}(2,-AB+1,-CD+1;\,-AD+2,-BC+2;\,1)}}{ \left( AD-1 \right) \left( BC-1 \right) }} $$ for the RHS of your supposed identity. $\endgroup$ – user64494 Feb 5 '17 at 16:20

This is inspired by Fedor's answer:

Consider $$ f(m):=-\frac{\binom{ab}{m}\binom{cd}{m}(m-bc)(m-ad)}{\binom{ad-1}{m}\binom{bc-1}{m}(a-c)(b-d)}. $$ Then $$ f(m+1)-f(m)=-\frac{\binom{ab}{m+1}\binom{cd}{m+1}(m+1-bc)(m+1-ad)}{\binom{ad-1}{m+1}\binom{bc-1}{m+1}(a-c)(b-d)}+\frac{\binom{ab}{m}\binom{cd}{m}(m-bc)(m-ad)}{\binom{ad-1}{m}\binom{bc-1}{m}(a-c)(b-d)}=- \frac{\binom{ab}{m}\binom{cd}{m}}{\binom{ad-1}{m}\binom{bc-1}{m}(a-c)(b-d)} \left(\frac{\frac{ab-m}{m+1}\frac{cd-m}{m+1}}{\frac{ad-1-m}{m+1}\frac{bc-1-m}{m+1}}(m+1-bc)(m+1-ad)-(m-bc)(m-ad)\right)=- \frac{\binom{ab}{m}\binom{cd}{m}}{\binom{ad-1}{m}\binom{bc-1}{m}(a-c)(b-d)}(m^2-m(ab+cd)+abcd-m^2+m(ad+bc)-abcd)=m\frac{\binom{ab}{m}\binom{cd}{m}}{\binom{ad-1}{m}\binom{bc-1}{m}}. $$ Thus, the sum $$ \sum_{m=0}^n m\frac{\binom{ab}{m}\binom{cd}{m}}{\binom{ad-1}{m}\binom{bc-1}{m}} $$ is equal $f(n+1)-f(0)$, which implies the identity you want.

| cite | improve this answer | |
  • $\begingroup$ I did not see the update to Fedor's post which appeared as I was typing the formulas; I'll leave this answer here anyway. $\endgroup$ – Vladimir Dotsenko Feb 5 '17 at 18:04

In addition to the Fedor's answer: Maple 2016 code

sum(m*binomial(k, m)*binomial(x*l/k, m)/(binomial(-l-1, m)*binomial(-x-1, m)), m = 0 .. k);

produces $${\frac {lxk}{{k}^{2}+lk+xk+xl}}. $$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.